Structure of the cystic fibrosis transmembrane conductance regulator in the inward-facing conformation revealed by single particle electron microscopy - Ateeq Al-Zahrani; Natasha Cant; Vassilis Kargas; Tracy Rimington; Luba Aleksandrov; John R. Riordan; Robert C. Ford (AIMS Biophysics, 2015)
The most common inherited disease in European populations is cystic fibrosis. Mutations in the gene lead to loss of function of the cystic fibrosis transmembrane conductance regulator protein (CFTR). CFTR is a member of the ATP-binding cassette family of membrane proteins that mostly act as active transporters using ATP to move substances across membranes. These proteins undergo large conformational changes during the transport cycle, consistent with an inward-facing to outward-facing translocation mechanism that was originally proposed by Jardetzky. CFTR is the only member of this family of proteins that functions as an ion channel, and in this case ATP and phosphorylation of a regulatory domain controls the opening of the channel. In this article we describe the inward-facing conformation of the protein and show it can be modulated by the presence of a purified recombinant NHERF1-PDZ1 domain that binds with high affinity to the CFTR C-terminal PDZ motif (-QDTRL). ATP hydrolysis activity of CFTR can also be modulated by glutathione, which we postulate may bind to the inward-facing conformation of the protein. A homology model for CFTR, based on a mitochondrial ABC transporter of glutathione in the inward-facing configuration has been generated. The map and the model are discussed with respect to the biology of the channel and the specific relationship between glutathione levels in the cell and CFTR. Finally, disease-causing mutations are mapped within the model and discussed in terms of their likely physiological effects.